Comparison between piezoelectric transformer and electromagnetic transformer used in electronic circuits - Wedian Hadi Abd Al Ameer; Mustafa A. Fadel Al-Qaisi; Ammar Al-Gizi (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2020)
This paper presents study, modeling and simulation of the piezoelectric material works as transformer (piezoelectric transformer (PT)) in power electronic circuits, comparisons are made with the regular transformer (iron core) works in the same circuit, the tested circuit is the full bridge converter which used in the simulation as dc power supply circuit. As a result, a detailed simulation for both the piezoelectric transformer and traditional transformer are achieved, as well as the output voltage from the dc power supply is tested by varying the load resistance. The dc power supply circuit has been simulated using PSIM (V9.1) power electronic circuit simulation software.